A water treatment filter material and a method of making the same
By combining modified polyacrylonitrile fiber membranes with covalent organic frameworks, water treatment filtration materials have solved the problems of poor mechanical properties and weak antifouling performance in membrane separation technology, achieving efficient and stable water treatment effects and self-cleaning performance.
Patent Information
- Application Number
- CN202511841211.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2045-12-09
AI Technical Summary
Existing membrane separation technologies in water treatment suffer from problems such as poor reusability, poor mechanical properties, membrane pore blockage, and poor antifouling performance, leading to membrane flux decline and shortened service life.
Water treatment filtration materials are prepared by using modified polyacrylonitrile fiber membranes and covalent organic framework growth solution reaction. By utilizing the photocatalytic properties and improved hydrophilicity of modified nano-titanium dioxide, combined with electrospinning and nano-spray loading technology, a stable covalent organic framework structure is formed, which improves antibacterial properties and filtration efficiency.
It achieves long-term water flux stability and high separation efficiency of water treatment filter materials, avoids membrane pore clogging and performance degradation, extends service life, and has a self-cleaning effect.
Abstract
Description
Technical Field
[0001] This invention relates to the field of filtration materials technology, specifically to a water treatment filtration material and its preparation method. Background Technology
[0002] With global population growth and industrialization, the demand for water resources is constantly increasing. Organic pollution and heavy metal pollution are currently the main sources of water pollution.
[0003] Wastewater treatment and recycling are considered key to solving water pollution problems and sustainably and effectively addressing water scarcity. Various water treatment methods exist, including oxidation, electrocoagulation, filtration, and chlorination, but these traditional methods are time-consuming and can generate secondary pollutants. Membrane filtration technology, which intersects with filtration, has gained widespread attention due to its advantages in water treatment, such as not generating secondary pollutants, high selectivity, high separation efficiency, and good stability. Over the past few decades, membrane filtration technology has developed rapidly and been widely applied, with various membrane processes used for water separation and purification, including microfiltration, ultrafiltration, nanofiltration, reverse osmosis, and forward osmosis. Filter membranes can remove most harmful substances from water, such as viruses, bacteria, microorganisms, algae, and other large organic molecules, as well as metal ions.
[0004] Membrane separation technology has been widely used in fields such as biology, medicine, and wastewater treatment. However, as an emerging technology, membrane separation still faces some challenges. Currently, commercially available filtration membranes suffer from poor reusability, weak mechanical properties, pore clogging, flux decay with long-term use, and poor antifouling performance. To improve the overall performance of membrane separation technology in practical applications, further improvements are needed in the performance of membrane materials. Summary of the Invention
[0005] The purpose of this invention is to provide a water treatment filtration material and its preparation method to solve the problems existing in the prior art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0007] A water treatment filtration material, wherein the water treatment filtration material is prepared by reacting a modified polyacrylonitrile fiber membrane in a covalent organic framework growth solution;
[0008] The modified polyacrylonitrile fiber membrane is prepared by electrospinning copolymerized modified polyacrylonitrile and then nano-spraying modified nano-titanium dioxide.
[0009] The copolymerized modified polyacrylonitrile is prepared by copolymerizing acrylonitrile with itaconic acid and ethylene 2-(methacryloyloxy)ethyl phosphate.
[0010] The modified nano-titanium dioxide is prepared by reacting copper-doped nano-titanium dioxide with KH-550;
[0011] The copper-doped nano-titanium dioxide is prepared by hydrothermal reaction of copper source with tetrabutyl titanate followed by calcination.
[0012] The covalent organic framework growth solution includes p-phenylenediamine, trialdehyde phloroglucinol, and 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine.
[0013] As an optimization, the copper source is one or more of copper nitrate, copper chloride, copper sulfate, basic copper carbonate, and copper oxalate.
[0014] A method for preparing a water treatment filter material includes the following preparation steps:
[0015] (1) By mass fraction, 2-3 parts acrylonitrile, 0.8-1.2 parts itaconic acid, 0.25-0.4 parts ethylene 2-(methacryloyloxy)ethyl phosphate, and 12-18 parts dimethyl sulfoxide are mixed evenly, and nitrogen gas is bubbled for 30-40 min. Under nitrogen atmosphere, the temperature is raised to 65-70℃, and 0.008-0.012 parts initiator are added. Then, the mixture is stirred at 65-70℃ and 200-300 r / min for 10-12 h. The mixture is then settled with acetone, washed, and vacuum dried at 60-70℃ for 10-12 h to obtain copolymerized modified polyacrylonitrile.
[0016] (2) Dissolve 0.07-0.09 parts of copper nitrate in 50-64 parts of mixed solvent by mass, add 9.7-12.4 parts of 50wt% tetrabutyl titanate ethanol solution at 2-3 drops per second, stir at 200-300 r / min for 100-120 min at room temperature, let stand for 60-70 min, transfer to reaction vessel, react at 160-170℃ for 5-6 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 50-60℃ for 8-10 h, calcine in muffle furnace at 450-500℃ for 2-2.5 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 50-60℃ for 6-8 h, grind through 400 mesh sieve to obtain copper-doped nano titanium dioxide;
[0017] (3) Mix 0.3-0.4 parts KH-550, 3-4 parts pure water and 40-50 parts anhydrous ethanol evenly according to the mass fraction, adjust the pH to 3.8-4.2, stir at 55-60℃ and 200-300 r / min for 50-60 min, add 0.7-0.9 parts copper-doped nano titanium dioxide, ultrasonically disperse for 10-12 min, stir and reflux at 70-75℃ and 300-400 r / min for 2-3 h, centrifuge and wash with ethanol aqueous solution with a volume ratio of 1:1, vacuum dry at 70-80℃ for 5-6 h, grind through a 400 mesh sieve to obtain modified nano titanium dioxide;
[0018] (4) After dissolving and degassing the copolymerized polyacrylonitrile with dimethyl sulfoxide, prepare a copolymerized polyacrylonitrile spinning solution of 12wt%~14wt%. Disperse the modified nano-titanium dioxide with anhydrous ethanol and sonicate for 15~20 min to obtain a modified nano-titanium dioxide dispersion of 2wt%~3wt%. Inject the copolymerized polyacrylonitrile spinning solution into a syringe with a propulsion speed of 0.9~1ml / h, a voltage of 18~20kV, and a distance of 15cm between the needle tip and the collecting roller. Place the atomizer containing the modified nano-titanium dioxide dispersion at the collecting roller with the spray direction of the atomizer perpendicular to the collecting roller. Spin for 7~8 h at 23~27℃ and 46%~54%RH. Peel off from the collecting roller and vacuum dry at 50~60℃ for 10~12 h to obtain a modified polyacrylonitrile fiber membrane.
[0019] (5) The modified polyacrylonitrile fiber membrane is immersed in the covalent organic framework growth solution at a bath ratio of 1:(150~200)g / ml. The reaction is carried out in a hydrothermal reactor at 115~125℃ for 48~50h. After natural cooling to room temperature, the membrane is taken out, washed with acetone, and vacuum dried at 60~70℃ for 10~12h to obtain the water treatment filter material.
[0020] As an optimization, the initiator in step (1) is one of azobisisobutyronitrile, benzoyl peroxide, and ammonium persulfate.
[0021] As an optimization, the reaction process of the copolymerized modified polyacrylonitrile in step (1) is as follows:
[0022] .
[0023] As an optimization, the mixed solvent in step (2) is obtained by mixing 40-50 parts of anhydrous ethanol, 10-12 parts of pure water, and 2-2.4 parts of 70wt% concentrated nitric acid evenly by mass.
[0024] As an optimization, the reaction process of the modified nano-titanium dioxide in step (3) is as follows:
[0025] .
[0026] As an optimization, the amount of modified nano-titanium dioxide dispersion in step (4) is 0.2 to 0.3 times the mass of the copolymerized modified polyacrylonitrile spinning solution.
[0027] As an optimization, the covalent organic framework growth solution in step (5) is prepared by uniformly mixing p-phenylenediamine, trialdehyde phloroglucinol, 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine, glacial acetic acid, and 1,4-dioxane in a mass ratio of 1:(1.5~1.6):(0.4~0.5):(16~20):(250~300).
[0028] As an optimization, the reaction process of the water treatment filter material in step (5) is as follows:
[0029] .
[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0031] In preparing the water treatment filtration material, this invention first copolymerizes acrylonitrile with itaconic acid and ethylene 2-(methacryloyloxy)ethyl phosphate to obtain copolymerized modified polyacrylonitrile; then, copper-doped nano-titanium dioxide is obtained by hydrothermal reaction of copper source with tetrabutyl titanate followed by calcination; modified nano-titanium dioxide is obtained by reacting copper-doped nano-titanium dioxide with KH-550; modified polyacrylonitrile fiber membrane is obtained by electrospinning the copolymerized modified polyacrylonitrile and nano-spray loading the modified nano-titanium dioxide; and finally, the modified polyacrylonitrile fiber membrane is reacted in a covalent organic framework growth solution to obtain the water treatment filtration material.
[0032] First, copolymerized polyacrylonitrile (PA) was prepared by copolymerizing acrylonitrile with itaconic acid and ethylene 2-(methacryloyloxy)ethyl phosphate. Then, itaconic acid segments and ethylene phosphate rings were introduced into the PA chain using solution polymerization. The copolymerization of itaconic acid introduced carboxylic acid groups into the PA, improving its hydrophilicity. Simultaneously, the carboxyl groups, being negatively charged, exhibited good electrostatic bonding capabilities. The ethylene phosphate rings, on the other hand, possessed the ability to react with tertiary amine groups to form phosphorylcholine-like structures. These phosphorylcholine-like structures, as zwitterionic groups, exhibited good hydrophilicity and, due to their similarity to phosphorylcholine structures, demonstrated excellent binding ability to bacterial surfaces, thus synergistically assisting the antibacterial structure in achieving better antibacterial performance.
[0033] Secondly, copper-doped nano-titanium dioxide was prepared by hydrothermal reaction of copper source with tetrabutyl titanate followed by calcination. Modified nano-titanium dioxide was then prepared by reacting copper-doped nano-titanium dioxide with KH-550. Introducing copper salts during the preparation of nano-titanium dioxide allows for the introduction of doped copper ions into the titanium dioxide lattice. Copper ion doping enhances the absorption of titanium dioxide in the visible light band, thereby improving the optical properties of nano-titanium dioxide. Furthermore, both copper ions and titanium dioxide possess good antibacterial properties, and copper ion doping can further improve these properties. However, copper-doped nano-titanium dioxide suffers from a common problem with nano-titanium dioxide: its excessively high surface polarity makes it prone to aggregation and difficult to process. To ensure uniform dispersion within the host, KH-550 was used to surface-modify copper-doped nano-titanium dioxide. The modified nano-titanium dioxide exhibited a slight decrease in hydrophilicity but remained uniformly dispersed within the host. Furthermore, the surface modification with KH-550 introduced reactive amino groups to the surface of the modified nano-titanium dioxide. On one hand, amino groups can connect with the carboxyl groups on the copolymerized polyacrylonitrile through hydrogen bonding, electrostatic bonding, and amidation reactions, thereby improving the loading strength of the modified nano-titanium dioxide on the host. On the other hand, amino groups can also provide reaction sites for the subsequent in-situ growth of covalent organic frameworks, increasing the loading rate of the covalent organic framework.
[0034] Finally, modified polyacrylonitrile fiber membranes were prepared by electrospinning copolymerized polyacrylonitrile and then nano-spraying modified nano-titanium dioxide onto the fibers. Electrospinning can form fiber membranes with good porosity and pore structure. Using nano-spraying technology to load modified nano-titanium dioxide simultaneously with electrospinning achieves better loading results because the nano-spraying loading is carried out concurrently during electrospinning, allowing the modified nano-titanium dioxide to be more evenly loaded onto the fibers of the modified polyacrylonitrile fiber membrane, resulting in better loading. Directly mixing modified nano-titanium dioxide into the spinning solution can lead to difficulties in dispersion and some modified nano-titanium dioxide being encapsulated within the fibers, hindering its effectiveness. Loading through impregnation post-treatment can easily result in uneven loading or only surface loading, leading to low loading levels and poor modification effects. Water treatment filter materials were prepared by reacting the modified polyacrylonitrile fiber membrane in a covalent organic framework growth solution. p-Phenylenediamine and trialdehyde-resorcinol self-assembled through the reaction of aldehyde and amino groups to form a two-dimensional covalent organic framework.In the initial assembly stage, the aldehyde and amino groups first connect via a reversible Schiff base reaction to form an unstable enol-imine structure. Subsequently, through irreversible tautomerism, this structure transforms into a stable β-enone amine structure. This stable structure obtained through irreversible isomerization overcomes the instability of the Schiff base bond, thus providing stable functional support during water treatment filtration. The amino groups introduced onto the modified nano-titanium dioxide can also serve as initial growth sites for the covalent organic framework. Simultaneously, the aldehyde groups, provided by trialdehyde phloroglucinol, can undergo the same tautomerism to form a stable connection structure, thereby ensuring stable growth on the modified nano-titanium dioxide. The modified polyacrylonitrile fiber membrane incorporates 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine with tertiary amine side chains into the monomers of the covalent organic framework. Besides its conventional role in the covalent organic framework structure, this tertiary amine side chain introduces a quaternary amine group into the framework. This tertiary amine group can undergo a quaternization-like reaction with the vinyl phosphate ring on the polyacrylonitrile segment to generate a phosphorylcholine-like structure, further enhancing hydrophilicity and providing another pathway for connection with the modified polyacrylonitrile fiber membrane. This further improves the negative effects of the covalent organic framework on the modified polyacrylonitrile fiber membrane. Load stability; the two-dimensional covalent organic framework, in situ self-assembled and grown on the modified polyacrylonitrile fiber membrane, forms finer sieving channels within the pores of the fiber membrane through its approximately 1.8 nm internal diameter. This allows for the separation of organic pollutants from water molecules in wastewater. Since most organic pollutants, such as dyes and antibiotics, are relatively large (their molecular diameter is much larger than the internal diameter of the covalent organic framework), they are unable to pass through the internal channels and are blocked. However, smaller water molecules are unrestricted and can pass normally through the covalent organic framework and the entire water treatment filter material, thus completing the wastewater treatment process. The filtration process is effective because the amino groups introduced into the modified nano-titanium dioxide result in the covalent organic framework growing in situ close to the modified nano-titanium dioxide. Organic pollutants blocked outside the covalent organic framework or clogged in the internal channels are quickly decomposed by the photocatalytically degradable nano-titanium dioxide, thus achieving a self-cleaning effect. Due to this ability to clean itself at any time and avoid clogging, the prepared water treatment filter material can maintain stable water flux and filtration efficiency for a long time without significantly reducing its performance over time, effectively extending the service life of the water treatment filter material. Detailed Implementation
[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] The raw material information used in all the following examples and comparative examples is as follows:
[0037] Initiator: Azobisisobutyronitrile;
[0038] Copper source: Copper nitrate;
[0039] Mixed solvent: By mass, it is obtained by mixing 45 parts anhydrous ethanol, 11 parts pure water and 2.2 parts 70wt% concentrated nitric acid evenly.
[0040] In all the following examples and comparative examples, the amount of modified nano-titanium dioxide dispersion used was 0.25 times the mass of the copolymerized modified polyacrylonitrile spinning solution.
[0041] Example 1: A method for preparing a water treatment filter material, the method comprising the following preparation steps:
[0042] (1) By mass, 2 parts acrylonitrile, 0.8 parts itaconic acid, 0.25 parts ethylene 2-(methacryloyloxy)ethyl phosphate and 12 parts dimethyl sulfoxide were mixed evenly, and nitrogen gas was bubbled for 30 min. Under nitrogen atmosphere, the temperature was raised to 65°C, 0.008 parts initiator were added, and then the mixture was stirred at 200 r / min at 65°C for 12 h. After precipitation with acetone and washing, the mixture was vacuum dried at 60°C for 12 h to obtain copolymerized modified polyacrylonitrile.
[0043] (2) Dissolve 0.07 parts of copper nitrate in 50 parts of mixed solvent by mass, add 9.7 parts of 50wt% tetrabutyl titanate ethanol solution at 2 drops per second. After the addition is completed, stir at 200 r / min for 120 min at room temperature, let stand and age for 60 min, transfer to a reaction vessel, react at 160℃ for 6 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 50℃ for 10 h, calcine at 450℃ in a muffle furnace for 2.5 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 50℃ for 8 h, grind through a 400 mesh sieve to obtain copper-doped nano titanium dioxide;
[0044] (3) According to the mass fraction, 0.3 parts KH-550, 3 parts pure water and 40 parts anhydrous ethanol are mixed evenly, the pH is adjusted to 3.8, stirred at 55℃ and 200r / min for 60min, 0.7 parts copper-doped nano titanium dioxide are added, ultrasonically dispersed for 10min, stirred and refluxed at 70℃ and 300r / min for 3h, washed by centrifugation with ethanol aqueous solution with a volume ratio of 1:1, vacuum dried at 70℃ for 6h, and ground through a 400-mesh sieve to obtain modified nano titanium dioxide;
[0045] (4) After dissolving and degassing the copolymerized polyacrylonitrile with dimethyl sulfoxide, a 12wt% copolymerized polyacrylonitrile spinning solution was prepared. The modified nano-titanium dioxide was dispersed with anhydrous ethanol and sonicated for 15 min to obtain a 2wt% modified nano-titanium dioxide dispersion. The copolymerized polyacrylonitrile spinning solution was injected into a syringe at a speed of 1 ml / h and a voltage of 18 kV. The distance between the needle tip and the collecting roller was 15 cm. The atomizer containing the modified nano-titanium dioxide dispersion was placed at the collecting roller with the spray direction of the atomizer perpendicular to the collecting roller. The spinning was carried out at 23℃ and 46%RH for 8 h. The fibers were peeled off from the collecting roller and vacuum dried at 50℃ for 12 h to obtain the modified polyacrylonitrile fiber membrane.
[0046] (5) A covalent organic framework growth solution was prepared by mixing p-phenylenediamine, trialdehyde phloroglucinol, 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine, glacial acetic acid, and 1,4-dioxane in a mass ratio of 1:1.5:0.4:16:250. The modified polyacrylonitrile fiber membrane was immersed in the covalent organic framework growth solution at a bath ratio of 1:150 g / ml. The membrane was reacted in a hydrothermal reactor at 115°C for 50 h. After naturally cooling to room temperature, the membrane was washed with acetone and dried under vacuum at 60°C for 12 h to obtain the water treatment filter material.
[0047] Example 2: A method for preparing a water treatment filter material, the method comprising the following preparation steps:
[0048] (1) By mass, 2.5 parts acrylonitrile, 1 part itaconic acid, 0.33 parts ethylene 2-(methacryloyloxy)ethyl phosphate and 15 parts dimethyl sulfoxide were mixed evenly, and nitrogen gas was bubbled for 35 min. Under nitrogen atmosphere, the temperature was raised to 70°C, 0.01 parts initiator were added, and then the mixture was stirred at 70°C and 250 r / min for 11 h. After precipitation with acetone and washing, the mixture was vacuum dried at 65°C for 11 h to obtain copolymerized modified polyacrylonitrile.
[0049] (2) Dissolve 0.08 parts of copper nitrate in 57 parts of mixed solvent by mass, add 11 parts of 50wt% tetrabutyl titanate ethanol solution at 2.5 drops per second. After the addition is completed, stir at 250 r / min for 110 min at room temperature, let stand and age for 65 min, transfer to a reaction vessel, react at 165℃ for 5.5 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 55℃ for 9 h, calcine at 450℃ in a muffle furnace for 2.5 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 55℃ for 7 h, grind through a 400 mesh sieve to obtain copper-doped nano titanium dioxide;
[0050] (3) By mass fraction, 0.35 parts KH-550, 3.5 parts pure water and 45 parts anhydrous ethanol were mixed evenly, the pH was adjusted to 4, and the mixture was stirred at 60℃ and 250 r / min for 55 min. 0.8 parts copper-doped nano titanium dioxide were added, and the mixture was ultrasonically dispersed for 11 min. The mixture was stirred and refluxed at 70℃ and 350 r / min for 2.5 h. The mixture was washed by centrifugation with an ethanol aqueous solution with a volume ratio of 1:1, and vacuum dried at 75℃ for 5.5 h. The mixture was then ground through a 400-mesh sieve to obtain modified nano titanium dioxide.
[0051] (4) After dissolving and degassing the copolymerized polyacrylonitrile with dimethyl sulfoxide, a 13wt% copolymerized polyacrylonitrile spinning solution was prepared. The modified nano-titanium dioxide was dispersed with anhydrous ethanol and sonicated for 18 min to obtain a 2.5wt% modified nano-titanium dioxide dispersion. The copolymerized polyacrylonitrile spinning solution was injected into a syringe at a speed of 0.95 ml / h and a voltage of 19 kV. The distance between the needle tip and the collecting roller was 15 cm. The atomizer containing the modified nano-titanium dioxide dispersion was placed at the collecting roller with the spray direction of the atomizer perpendicular to the collecting roller. The spinning was carried out at 25℃ and 50% RH for 7.5 h. The fibers were then peeled off from the collecting roller and vacuum dried at 55℃ for 11 h to obtain the modified polyacrylonitrile fiber membrane.
[0052] (5) A covalent organic framework growth solution was prepared by mixing p-phenylenediamine, trialdehyde phloroglucinol, 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine, glacial acetic acid, and 1,4-dioxane in a mass ratio of 1:1.55:0.45:18:275. The modified polyacrylonitrile fiber membrane was immersed in the covalent organic framework growth solution at a bath ratio of 1:175 g / ml. The membrane was reacted in a hydrothermal reactor at 120°C for 49 h. After naturally cooling to room temperature, the membrane was washed with acetone and dried under vacuum at 65°C for 11 h to obtain a water treatment filter material.
[0053] Example 3: A method for preparing a water treatment filter material, the method comprising the following preparation steps:
[0054] (1) By mass, 3 parts acrylonitrile, 1.2 parts itaconic acid, 0.4 parts ethylene 2-(methacryloyloxy)ethyl phosphate and 18 parts dimethyl sulfoxide were mixed evenly, and nitrogen gas was bubbled for 40 min. Under nitrogen atmosphere, the temperature was raised to 70°C, 0.012 parts initiator were added, and then the mixture was stirred at 300 r / min at 70°C for 10 h. After precipitation with acetone and washing, the mixture was vacuum dried at 70°C for 10 h to obtain copolymerized modified polyacrylonitrile.
[0055] (2) Dissolve 0.09 parts of copper nitrate in 64 parts of mixed solvent by mass, and add 12.4 parts of 50wt% tetrabutyl titanate ethanol solution at 3 drops per second. After the addition is completed, stir at 300 r / min for 100 min at room temperature, let stand and age for 70 min, transfer to a reaction vessel, react at 170℃ for 5 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 60℃ for 8 h, calcine at 500℃ in a muffle furnace for 2 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, dry under vacuum at 60℃ for 6 h, grind through a 400 mesh sieve to obtain copper-doped nano titanium dioxide;
[0056] (3) According to the mass fraction, 0.4 parts KH-550, 4 parts pure water and 50 parts anhydrous ethanol are mixed evenly, the pH is adjusted to 4.2, stirred at 60℃ and 300r / min for 50min, 0.9 parts copper-doped nano titanium dioxide are added, ultrasonically dispersed for 12min, stirred and refluxed at 75℃ and 400r / min for 2h, washed by centrifugation with ethanol aqueous solution with a volume ratio of 1:1, vacuum dried at 80℃ for 5h, and ground through a 400-mesh sieve to obtain modified nano titanium dioxide;
[0057] (4) After dissolving and degassing the copolymerized polyacrylonitrile with dimethyl sulfoxide, a 14wt% copolymerized polyacrylonitrile spinning solution was prepared. The modified nano-titanium dioxide was dispersed with anhydrous ethanol and sonicated for 20 min to obtain a 3wt% modified nano-titanium dioxide dispersion. The copolymerized polyacrylonitrile spinning solution was injected into a syringe at a speed of 0.9 ml / h and a voltage of 20 kV. The distance between the needle tip and the collecting roller was 15 cm. The atomizer containing the modified nano-titanium dioxide dispersion was placed at the collecting roller with the spray direction of the atomizer perpendicular to the collecting roller. The spinning was carried out at 27℃ and 54%RH for 7 h. The fibers were peeled off from the collecting roller and vacuum dried at 60℃ for 10 h to obtain the modified polyacrylonitrile fiber membrane.
[0058] (5) A covalent organic framework growth solution was prepared by mixing p-phenylenediamine, trialdehyde phloroglucinol, 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine, glacial acetic acid, and 1,4-dioxane in a mass ratio of 1:1.6:0.5:20:300. The modified polyacrylonitrile fiber membrane was immersed in the covalent organic framework growth solution at a bath ratio of 1:200 g / ml. The membrane was reacted in a hydrothermal reactor at 125°C for 48 h. After naturally cooling to room temperature, the membrane was washed with acetone and dried under vacuum at 70°C for 10 h to obtain a water treatment filter material.
[0059] Comparative Example 1:
[0060] The difference between the preparation method of the water treatment filter material in Comparative Example 1 and Example 2 lies in step (1). Step (1) is modified as follows: 2.5 parts by mass of acrylonitrile, 1 part itaconic acid, and 15 parts dimethyl sulfoxide are mixed evenly, bubbled with nitrogen for 35 min, heated to 70°C under a nitrogen atmosphere, 0.01 parts of initiator are added, and then stirred at 70°C and 250 r / min for 11 h. After precipitation with acetone and washing, the mixture is vacuum dried at 65°C for 11 h to obtain copolymerized modified polyacrylonitrile. The remaining steps are the same as in Example 2.
[0061] Comparative Example 2:
[0062] The difference between the preparation method of the water treatment filter material in Comparative Example 2 and Example 2 lies in the difference in steps (2) and (3). Step (2) is modified as follows: Take 57 parts of mixed solvent by mass, add 11 parts of 50wt% tetrabutyl titanate ethanol solution at 2.5 drops per second. After the addition is completed, stir at 250 r / min for 110 min at room temperature, let stand and age for 65 min, transfer to a reaction vessel, react at 165℃ for 5.5 h, cool naturally to room temperature, wash with anhydrous ethanol by centrifugation, vacuum dry at 55℃ for 9 h, calcine at 450℃ in a muffle furnace for 2.5 h, cool naturally to room temperature, and wash with anhydrous ethanol. Centrifuge and wash, vacuum dry at 55℃ for 7h, grind through a 400-mesh sieve to obtain nano-titanium dioxide; modify step (3) as follows: mix 0.35 parts KH-550, 3.5 parts pure water, and 45 parts anhydrous ethanol by mass, adjust the pH to 4, stir at 60℃ and 250r / min for 55min, add 0.8 parts nano-titanium dioxide, ultrasonically disperse for 11min, stir and reflux at 70℃ and 350r / min for 2.5h, centrifuge and wash with an ethanol-water solution with a volume ratio of 1:1, vacuum dry at 75℃ for 5.5h, grind through a 400-mesh sieve to obtain modified nano-titanium dioxide. The remaining steps are the same as in Example 2.
[0063] Comparative Example 3:
[0064] The preparation method of the water treatment filter material in Comparative Example 3 differs from that in Example 2 in that step (3) is omitted, and step (4) is modified as follows: the copolymerized modified polyacrylonitrile is dissolved and degassed with dimethyl sulfoxide to prepare a 13wt% copolymerized modified polyacrylonitrile spinning solution. Copper-doped nano-titanium dioxide is dispersed with anhydrous ethanol and sonicated for 18 min to obtain a 2.5wt% copper-doped nano-titanium dioxide dispersion. The copolymerized modified polyacrylonitrile spinning solution is injected into a syringe at a speed of 0.95 ml / h, a voltage of 19 kV, and a distance of 15 cm between the needle tip and the collecting roller. The atomizer containing the copper-doped nano-titanium dioxide dispersion is placed at the collecting roller with the spray direction of the atomizer perpendicular to the collecting roller. The spinning is carried out at 25°C and 50% RH for 7.5 h. The material is then peeled off from the collecting roller and vacuum dried at 55°C for 11 h to obtain a modified polyacrylonitrile fiber membrane. The amount of copper-doped nano-titanium dioxide dispersion is 0.25 times the mass of the copolymerized modified polyacrylonitrile spinning solution. The remaining steps are the same as in Example 2.
[0065] Comparative Example 4:
[0066] The difference between the preparation method of the water treatment filter material in Comparative Example 4 and Example 2 lies in step (4). Step (4) is modified as follows: after dissolving and degassing the copolymerized polyacrylonitrile with dimethyl sulfoxide, a 13wt% copolymerized polyacrylonitrile spinning solution is prepared. The copolymerized polyacrylonitrile spinning solution is injected into a syringe at a speed of 0.95 ml / h, a voltage of 19 kV, and a distance of 15 cm between the needle tip and the collecting roller. Spinning is carried out at 25°C and 50% RH for 7.5 h. The solution is then peeled off from the collecting roller and vacuum dried at 55°C for 11 h to obtain the modified polyacrylonitrile fiber membrane. The remaining steps are the same as in Example 2.
[0067] Comparative Example 5:
[0068] The difference between the preparation method of the water treatment filter material in Comparative Example 5 and Example 2 lies in step (4). Step (4) is modified as follows: the copolymerized modified polyacrylonitrile is dissolved in dimethyl sulfoxide, and then modified nano-titanium dioxide is added for ultrasonic dispersion. After degassing, a spinning solution containing 13 wt% copolymerized modified polyacrylonitrile and 0.625 wt% modified nano-titanium dioxide is prepared. The spinning solution is injected into a syringe at a speed of 0.95 ml / h, a voltage of 19 kV, and a distance of 15 cm between the needle tip and the collecting roller. Spinning is carried out at 25°C and 50% RH for 7.5 h. The solution is then peeled off from the collecting roller and vacuum dried at 55°C for 11 h to obtain the modified polyacrylonitrile fiber membrane. The remaining steps are the same as in Example 2.
[0069] Comparative Example 6:
[0070] The difference between the preparation method of the water treatment filter material in Comparative Example 6 and Example 2 lies in the different step (4). Step (4) is modified as follows: after dissolving and degassing the copolymerized modified polyacrylonitrile with dimethyl sulfoxide, a 13wt% copolymerized modified polyacrylonitrile spinning solution is prepared. The modified nano-titanium dioxide is dispersed with anhydrous ethanol and sonicated for 18 min to obtain a 2.5wt% modified nano-titanium dioxide dispersion. The copolymerized modified polyacrylonitrile spinning solution is injected into a syringe at a speed of 0.95 ml / h, a voltage of 19 kV, and a distance of 15 cm between the needle tip and the collecting roller. The spinning is carried out at 25°C and 50% RH for 7.5 h. The solution is then peeled off from the collecting roller and vacuum dried at 55°C for 11 h to obtain a polyacrylonitrile fiber membrane. The polyacrylonitrile fiber membrane is immersed in the modified nano-titanium dioxide dispersion at a bath ratio of 1:50 g / ml and left to stand for 2 h. It is then taken out, washed with anhydrous ethanol, and vacuum dried at 55°C for 7 h to obtain a modified polyacrylonitrile fiber membrane. The remaining steps are the same as in Example 2.
[0071] Comparative Example 7:
[0072] The difference between the preparation method of the water treatment filter material in Comparative Example 7 and Example 2 lies in step (5). Step (5) is modified as follows: the modified polyacrylonitrile fiber membrane is immersed in 1,4-dioxane at a bath ratio of 1:175 g / ml in a hydrothermal reactor at 120°C for 49 h, then naturally cooled to room temperature, removed and washed with acetone, and vacuum dried at 65°C for 11 h to obtain the water treatment filter material. The remaining steps are the same as in Example 2.
[0073] Test Example 1:
[0074] Antibacterial and photocatalytic degradation performance tests: The antibacterial rate and degradation rate of dye molecule pollutants of the prepared water treatment filter material were tested to evaluate its antibacterial and photocatalytic degradation performance. The specific test methods are as follows:
[0075] Antibacterial performance: The shaking method in GB / T 20944.3-2008 was used. The prepared water treatment filter material was mixed with bacterial solution at a sample size of 0.75±0.05g and shaken for 5min. The shaken bacterial solution was then cultured in agar medium. The inhibition rate of the water treatment filter material against Escherichia coli and Staphylococcus aureus was determined by the number of colonies. Each group of samples was tested 5 times and the average value was recorded.
[0076] Dye molecule degradation rate: A 5 mg / L Rhodamine B solution was prepared and stored in a dark place. 80 mg of water treatment filter material was dispersed in 100 ml of the Rhodamine B solution. The solution was stirred at 400 rpm for 5 hours in the dark, followed by photocatalytic reaction under light irradiation. A 300 W Xe lamp was used as the light source to simulate sunlight. After 2 hours, the concentration of remaining Rhodamine B in the solution was measured, and the degradation rate was calculated.
[0077] The results are shown in Table 1.
[0078] Table 1
[0079] ;
[0080] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-7 in Table 1 reveals that the water treatment filter material prepared by this invention has good antibacterial properties and high efficiency in degrading organic pollutants.
[0081] By comparing the data in the table, the data in Comparative Example 1 shows that during the preparation of copolymerized modified polyacrylonitrile, ethylene phosphate rings were successfully introduced into the polyacrylonitrile chain by copolyethylene 2-(methacryloyloxy)ethyl phosphate. The ethylene phosphate rings can react with the tertiary amine side chains on the covalent organic framework monomers to form a phosphorylcholine-like structure. This structure has better hydrophilicity and bacterial binding, and can effectively synergize with copper-doped modified titanium dioxide to exert its antibacterial effect, thereby improving antibacterial performance.
[0082] By comparing the data in the table, the data in Comparative Example 2 shows that copper doping with copper salts during the preparation of nano-titanium dioxide successfully improved the photocatalytic performance of nano-titanium dioxide, effectively enhanced its absorption effect in the visible light range, and greatly expanded its application range. The doped copper ions also have good antibacterial properties, which can synergistically improve the antibacterial effect.
[0083] By comparing the data in the table, the data in Comparative Example 3 shows that modifying copper-doped nano-titanium dioxide with KH-550 improves its dispersibility in the polyacrylonitrile matrix and avoids the performance degradation caused by agglomeration.
[0084] By comparing the data in the table, the data in Comparative Example 4 shows that the addition of modified nano-titanium dioxide effectively improves the antibacterial effect and the photocatalytic degradation ability of organic matter. The phosphorylcholine-like structure itself does not have much antibacterial performance, and it needs to work synergistically with modified nano-titanium dioxide, which has direct antibacterial properties, to enable it to exert better antibacterial performance.
[0085] The data comparison in the table shows that when nano-spray technology is not used to load and modify nano-titanium dioxide, the modification effect is poor and the dispersion is uneven, which directly leads to a decline in product performance.
[0086] By comparing the data in the table, the data in Comparative Example 7 shows that during the growth of the covalent organic framework, the tertiary amine group it carries reacts with the ethylene phosphate ring to form a phosphorylcholine-like structure, which can synergistically modify nano-titanium dioxide to provide better antibacterial properties.
[0087] Test Example 2:
[0088] Filtration and Recycling Performance Testing: The separation efficiency of the prepared water treatment filter material for organic pollutants and its separation efficiency after long-term circulation are tested to evaluate its filtration performance and recycling performance. The specific test methods are as follows:
[0089] Filtration performance: Dead-end filtration is employed, with a syringe pump providing the injection solution. A stable injection rate is maintained by varying the transmembrane pressure. The syringe pump operates between 0.5 and 3 bar. 10 mg / L methylene blue and 10 mg / L tetracycline solutions are prepared as organic contaminant test solutions, and their concentrations are determined using UV-Vis absorption spectroscopy. The flow rate is controlled at 600 L / (m²). 2 •h), the injection volume of organic pollution test solution is 150ml. Take the organic pollution test solution before and after filtration to measure its concentration and calculate the rejection rate. Each group is tested in parallel five times and the average value is recorded.
[0090] Recycling performance: Referring to the test method for filtration performance, the concentration of organic pollutant test solution was controlled at 10 mg / L. Methylene blue and tetracycline were selected for testing, and the flow rate was controlled at 600 L / (m³). 2 The test cycle consisted of 8 hours of continuous filtration followed by a 30-minute break, and 20 cycles were performed. A 300W Xe lamp was used as the light source throughout the test to simulate sunlight irradiation of the water treatment filter material. The concentration of organic pollutants in the test solution before filtration and after the last cycle was measured, and the cycle rejection rate was calculated. Each group was tested in parallel five times, and the average value was recorded.
[0091] The results are shown in Table 2.
[0092] Table 2
[0093] ;
[0094] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-7 in Table 2 reveals that the water treatment filter material prepared by this invention has good filtration performance for organic pollutants and good recyclability.
[0095] By comparing the data in the table, the data in Comparative Example 1 shows that during the preparation of copolymerized modified polyacrylonitrile, ethylene phosphate rings were successfully introduced into the polyacrylonitrile chain by copolyethylene 2-(methacryloyloxy)ethyl phosphate. The ethylene phosphate rings can react with the tertiary amine side chains on the covalent organic framework monomers to form phosphorylcholine-like structures. This provides more ways to fix the covalent organic framework, improves the load stability of the covalent organic framework on the surface of water treatment filter materials, and thus improves the retention rate and circulation retention rate of organic pollutants.
[0096] By comparing the data in the table, the data in Comparative Example 2 shows that copper doping with copper salts during the preparation of nano-titanium dioxide successfully improved the photocatalytic performance of nano-titanium dioxide, effectively enhancing its absorption capacity in the visible light range. Although it had little impact on the initial filtration effect of organic pollutants, it effectively ensured the stability of its filtration effect in the cycle experiment. This indicates that during continuous filtration, the photocatalytic degradation capability decomposes the organic pollutants intercepted and blocked on the surface of the water treatment filter material in real time, thereby ensuring stable filtration performance under long-term operation and improving the cycle life.
[0097] By comparing the data in the table, the data in Comparative Example 3 shows that modifying copper-doped nano-titanium dioxide with KH-550 improves its dispersibility in the polyacrylonitrile matrix and avoids the performance degradation caused by agglomeration. At the same time, the in-situ growth sites of the covalent organic framework are lost, resulting in it being connected only through phosphorylcholine-like structures, which greatly reduces the load stability and leads to performance degradation.
[0098] By comparing the data in the table, the data in Comparative Example 4 shows that the addition of modified nano-titanium dioxide endows the water treatment filter material with the ability to photocatalytically degrade organic pollutants and provides in-situ growth sites for covalent organic frameworks. The photocatalytic degradation ability allows it to decompose the organic pollutants intercepted and blocked on the surface of the water treatment filter material in real time, thereby ensuring stable filtration performance under long-term operation and improving cycle life. The in-situ growth sites for covalent organic frameworks effectively improve the load stability of covalent organic frameworks and effectively improve the filtration effect.
[0099] The data comparison in the table shows that when nano-spray technology is not used to load and modify nano-titanium dioxide, the modification effect is poor and the dispersion is uneven, which directly leads to a decline in product performance.
[0100] By comparing the data in the table, the data in Comparative Example 7 shows that the in-situ growth of covalent organic frameworks on the surface of water treatment filter materials effectively improves the separation efficiency of organic pollutants. Through the combination of size sieving effect and electrostatic repulsion effect, it retains and separates most of the organic pollutants, providing good water treatment filtration performance.
[0101] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A water treatment filter material, characterized by, The water treatment filter material is prepared by reacting modified polyacrylonitrile fiber membrane in a covalent organic framework growth solution. The modified polyacrylonitrile fiber membrane is prepared by electrospinning and nano-spray loading of modified nano-titanium dioxide on copolymerized modified polyacrylonitrile. The copolymerized modified polyacrylonitrile is prepared by copolymerizing acrylonitrile, itaconic acid and 2-(methacryloyloxy)ethyl phosphate. The modified nano-titanium dioxide is prepared by reacting copper-doped nano-titanium dioxide with KH-550. The copper-doped nano-titanium dioxide is prepared by hydrothermal reaction of a copper source and tetrabutyl titanate and then calcination. The covalent organic framework growth solution comprises p-phenylenediamine, triformylphloroglucinol and 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine.
2. The water treatment filter material of claim 1, wherein The copper source is one or more of copper nitrate, copper chloride, copper sulfate, basic copper carbonate and copper oxalate.
3. A method of producing the water treatment filter material according to claim 1, characterized by, The preparation steps include: (1) mixing acrylonitrile, itaconic acid and 2-(methacryloyloxy)ethyl phosphate, bubbling nitrogen gas, adding an initiator under a nitrogen atmosphere, then stirring and reacting, settling, washing and drying to prepare copolymerized modified polyacrylonitrile; (2) dissolving copper nitrate in a mixed solvent, adding tetrabutyl titanate ethanol solution dropwise, stirring at room temperature after dropwise addition is completed, aging, transferring to a reaction kettle, reacting, cooling, washing, drying, calcining, cooling, washing, drying, grinding and sieving to prepare copper-doped nano-titanium dioxide; (3) mixing KH-550, pure water and anhydrous ethanol, adjusting pH, stirring, adding copper-doped nano-titanium dioxide, dispersing, stirring and refluxing, washing, drying, grinding and sieving to prepare modified nano-titanium dioxide; (4) dissolving copolymerized modified polyacrylonitrile with dimethyl sulfoxide, degassing, preparing copolymerized modified polyacrylonitrile spinning solution, dispersing modified nano-titanium dioxide with anhydrous ethanol to prepare modified nano-titanium dioxide dispersion, injecting the copolymerized modified polyacrylonitrile spinning solution into a syringe, placing an atomizer containing the modified nano-titanium dioxide dispersion at a collecting roller, making the atomizer spray direction orthogonal to the collecting roller, electrospinning, peeling and drying to prepare modified polyacrylonitrile fiber membrane; (5) immersing the modified polyacrylonitrile fiber membrane in a covalent organic framework growth solution, reacting in a hydrothermal kettle, cooling, washing and drying to prepare a water treatment filter material.
4. The method of claim 3, wherein the water treatment filter material is prepared by the steps of: In step (1), the copolymerized modified polyacrylonitrile is prepared by uniformly mixing 2-3 parts of acrylonitrile, 0.8-1.2 parts of itaconic acid, 0.25-0.4 parts of 2-(methacryloyloxy)ethyl phosphate and 12-18 parts of dimethyl sulfoxide, bubbling nitrogen gas for 30-40 min, heating to 65-70°C under a nitrogen atmosphere, adding 0.008-0.012 parts of an initiator, then stirring and reacting at 65-70°C for 10-12 h, settling, washing, vacuum drying for 10-12 h and then preparing.
5. The method for preparing a water treatment filter material according to claim 3, characterized in that, The copper-doped nano-titania in step (2) is prepared as follows: 0.07-0.09 parts of copper nitrate is dissolved in 50-64 parts of mixed solvent, 9.7-12.4 parts of 50wt% tetrabutyl titanate ethanol solution is added dropwise at 2-3 drops per second, after the dropwise addition is completed, stirring is carried out at room temperature for 100-120 min, standing and aging is carried out for 60-70 min, it is transferred into a reaction kettle, reaction is carried out at 160-170℃ for 5-6 h, it is naturally cooled to room temperature, centrifugal washing is carried out, vacuum drying is carried out for 8-10 h, calcination is carried out in a muffle furnace at 450-500℃ for 2-2.5 h, it is naturally cooled to room temperature, centrifugal washing is carried out, vacuum drying is carried out for 6-8 h, and grinding is carried out through a 400 mesh sieve to obtain the copper-doped nano-titania.
6. The method of claim 3, wherein the water treatment filter material is prepared by the steps of: The mixed solvent in step (2) is prepared as follows: 40-50 parts of anhydrous ethanol, 10-12 parts of pure water and 2-2.4 parts of 70wt% concentrated nitric acid are uniformly mixed to obtain the mixed solvent.
7. The method for preparing a water treatment filter material according to claim 3, characterized in that, The modified nano-titania in step (3) is prepared as follows: 0.3-0.4 parts of KH-550, 3-4 parts of pure water and 40-50 parts of anhydrous ethanol are uniformly mixed, the pH is adjusted to 3.8-4.2, stirring is carried out at 55-60℃ for 50-60 min, 0.7-0.9 parts of copper-doped nano-titania is added, ultrasonic dispersion is carried out for 10-12 min, stirring and reflux reaction are carried out at 70-75℃ for 2-3 h, centrifugal washing is carried out, vacuum drying is carried out for 5-6 h, and grinding is carried out through a 400 mesh sieve to obtain the modified nano-titania.
8. The method for preparing a water treatment filter material according to claim 3, characterized in that, The modified polyacrylonitrile fiber membrane in step (4) is prepared as follows: after dimethyl sulfoxide is used to dissolve and deaerate the copolymerized modified polyacrylonitrile, a copolymerized modified polyacrylonitrile spinning solution with a concentration of 12wt%-14wt% is prepared, the modified nano-titania is dispersed in anhydrous ethanol and ultrasonic dispersion is carried out for 15-20 min to obtain a modified nano-titania dispersion liquid with a concentration of 2wt%-3wt%, the copolymerized modified polyacrylonitrile spinning solution is injected into a syringe, the pushing speed is 0.9-1 ml / h, the voltage is 18-20 kV, the distance between the needle tip and the collecting drum is 15 cm, the atomizer containing the modified nano-titania dispersion liquid is placed at the collecting drum, the atomizer spraying direction is orthogonal to the collecting drum, the spinning is carried out at 23-27℃ and 46%-54% RH for 7-8 h, the modified polyacrylonitrile fiber membrane is peeled off from the collecting drum, and vacuum drying is carried out for 10-12 h to obtain the modified polyacrylonitrile fiber membrane.
9. The method for preparing a water treatment filter material according to claim 3, characterized in that, The water treatment filter material in step (5) is prepared as follows: the modified polyacrylonitrile fiber membrane is immersed in a covalent organic framework growth solution according to a bath ratio of 1:(150-200) g / ml, reaction is carried out in a hydrothermal kettle at 115-125℃ for 48-50 h, it is naturally cooled to room temperature, taken out and washed, and vacuum drying is carried out for 10-12 h to obtain the water treatment filter material.
10. The method for preparing a water treatment filter material according to claim 3, characterized in that, The covalent organic framework growth solution in step (5) is prepared as follows: p-phenylenediamine, triformylphloroglucinol, 2-[[[2-(dimethylamino)ethyl]amino]methyl]-1,4-p-phenylenediamine, glacial acetic acid and 1,4-dioxane are uniformly mixed according to a mass ratio of 1:(1.5-1.6):(0.4-0.5):(16-20):(250-300) to obtain the covalent organic framework growth solution.
Citation Information
Patent Citations
Method for preparing polyacrylonitrile hollow fiber membrane
CN103521098A
Polyacrylonitrile hollow fiber ultrafiltration membrane and preparing method thereof
CN106268371A
